Hukum International Sebagai Lex Causae oleh Badan Arbitrase Komersial Internasional - Adolf, Huala (Indonesian Journal of International Law, 2021)
This article discusses whether international law may be applied as lex causae by arbitral body. The international instrument used as comparative study are the Model Arbitration Law 1985, UNCITRAL Arbitration RUles, the ICC Rules of Arbitration the ICSID Convention and the Indonesian National Law on Arbitration. The article suggest that although international law seems inappropriate to deal with commercial matters, in certain circumstances, it is possible.